2021
DOI: 10.1186/s41120-021-00046-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of O/W nano-emulsion containing nettle and fenugreek extract and cumin essential oil for evaluating antidiabetic properties

Abstract: The oil-in-water (O/W) nano-emulsion (NE) is expanded to enhance the bioavailability of hydrophobic compounds. The NE can be prepared by herbal extract and essential oil as herbal medicines for antidiabetic treatment. In the present study, the O/W NE was prepared by fenugreek extract (FE), nettle extract (NE), and cumin essential oil (CEO) using tween 80 and span 80 surfactants in an ultrasonic bath, at room temperature within 18 min. The antidiabetic property was evaluated by determining glucose absorption us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The study's findings offer unmistakable proof that NE is a plant medication with antidiabetic effects. A strong candidate for biomedical applications is the NE (Javadi et al., 2021 ).…”
Section: Applications Of Fenugreek Seeds In Nanotechnologymentioning
confidence: 99%
“…The study's findings offer unmistakable proof that NE is a plant medication with antidiabetic effects. A strong candidate for biomedical applications is the NE (Javadi et al., 2021 ).…”
Section: Applications Of Fenugreek Seeds In Nanotechnologymentioning
confidence: 99%
“…In three different types of nanoemulsion, the o/w type nanoemulsion consists of the water phase and oil phase. Then, surfactants are used for both hydrophilic and hydrophobic parts which stabilize the droplet emulsion and prevent phase separation [9,10]. Due to the low energy requirements, easy processing, low cost, and small droplets, the ultrasonic homogenizers method is commonly used for the synthesis of nanoemulsion.…”
Section: Synthesis Of Medicinal Plant-based Metal Nanoparticles and N...mentioning
confidence: 99%
“…This resulted in a significant blood glucose-lowering effect by NEs compared with free α-eleostearic acid, and the increased stability of α-eleostearic in nanoemulsions at the end of the 12-week storage period was observed [ 172 ]. Recently, Javadi et al showed that plant extract (fenugreek extract, nettle extract, and cumin essential oil)-loaded NEs had suitable stability, and a study on L6 cells demonstrated that plant extract-NEs could diminish blood sugar [ 224 ]. In another study, the Abelmoschus esculentus ethanolic extract nanoemulsion was prepared and orally administered to diabetic mice at a dose of 400 mg/kg body weight for 14 days.…”
Section: Current Lipid- and Inorganic-based (Metal Or Metal Oxide) Na...mentioning
confidence: 99%